GROUNDWATER SELF-CLEARING FROM 90SR WITHIN BACKGROUND AREA AND OWING TO ARTIFICIAL CONTAMINATION - Shevchenko, O.; Dolin, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The main idea of the presented results is the determination of spatial-temporal regularities of 90Sr content in groundwaters within Chornobyl Exclusion Zone. Utilization of formal kinetic regularities (of I order for irreversible process) for monitoring data analyses has been substantiated. Rate constants of groundwater self-clearing from 90Sr in dependence of type of contamination are calculated by iteration method. Graphic interpretation of data has been realized using package for analysis of Microsoft Excel and Statistica software. Self-clearing of groundwaters is carried out owing to three main processes: sorption as function of water containing medium dispercity, dispersion due to water exchange, concentration dilution (dissolving) of radionuclides in specified volume, and physical decay. considered Self-clearing is considered to be an important element both for the security and vulnerability of groundwaters. Data on 90Sr content in groundwater of background areas, in affected zone of radioactive waste storage, zone of groundwater nutrition from cooling pond of Chornobyl NPP, spots of primarily radioactive contamination, and of groundwater secondary contamination owing to well drilling are discussed. Rate constants for groundwater self-clearing from 90Sr are calculated from experimental data both for non-stationary (rapid) and stationary (slow) processes. The “half-decontamination” period (in analogy to half-life) is less than 0.5 year. The rate constant for unstable process two times, and for established one time exceeds the decay constant. The rates of groundwater self-clearing from strontium-90 owing to water exchange and geochemically immobilization are determined. The equilibrium of sorption-desorption within water saturated zone is generally depended on the rate of water exchange and radionuclides concentration in upper stream, i.e. from concentration gradient.